Computationally probing the performance of hybrid, heterogeneous and homogeneous Ir-based catalysts for water oxidation - Garcia Melchor, Max (My University, 2016)
An attractive strategy to improve the performance of water oxidation catalysts would be to anchor a homogeneous molecular catalyst on a heterogeneous solid surface to create a hybrid catalyst. The idea of this combined system is to take advantage of the individual properties of each of the two catalyst components. We use Density Functional Theory to determine the stability and activity of a model hybrid water oxidation catalyst consisting of a dimeric Ir complex attached on the IrO2(110) surface through two oxygen atoms. We find that homogeneous catalysts can be bound to its matrix oxide without losing significant activity. Hence, designing hybrid systems that benefit from both the high tunability of activity of homogeneous catalysts and the stability of heterogeneous systems seems feasible.
PUBLISHED
Journal Cover
Keywords: Density Functional Theory; Heterogeneous catalysis; Homogeneous catalysis; Iridium; Reaction mechanisms